Strengthening the Capacity of Border Health Centers for National Health Resilience - Hanifa, Yumna Nur Millati (BKM Public Health and Community Medicine, 2024)
Purpose: Community health centers in border areas have a crucial role in preserving public health and preventing the transmission of infectious diseases considering that border areas are place of high mobility for entry and departure ports. Community health centers may ensure national health security and improve public confidence in healthcare by detecting outbreaks early and effectively preventing outbreaks at borders. This concept aims to improve national health resilience by strengthening the capabilities of health centers on the border. Content: Using a contingency theory approach, capacity strengthening is carried out by adapting strategies based on the specific conditions for each border health center. This concept includes increasing human resources through training, procurement of advanced medical equipment and facilities, development of integrated health information and management systems, and increasing cross-sectoral cooperation. Analysis of health data, tracking of disease cases, and community satisfaction surveys on border health center services are used in the evaluation process. Limited infrastructure and human resources will be a challenge, but support from the government, cross-sectoral cooperation, and health worker training will be the significant enablers or facilitators. However, this may impact communities by reducing health risks, increasing national health resilience, and improving trust in healthcare systems. Therefore, strengthening the capacity of border health centers is an intelligent strategy to protect public health and minimize the financial impact of disease outbreaks.